2022
DOI: 10.1177/00494755221076649
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cataract and factors associated with cataract surgery uptake among older persons in Malaysia: A cross-sectional study from the National Eye Survey II

Abstract: Nationally-representative evidence is limited on factors affecting uptake of cataract surgery in Malaysia. We found the prevalence of cataract among older persons to be 26.8%. The two most common barriers were ‘need not felt’ (43.5%) and ‘fear of surgery or poor result’ (16.2%). Reluctance for surgical intervention was greater outside the Central zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Our results also showed that female patients constituted more than 50% of all cataract surgery patients each year, and the age-adjusted rate of cataract surgery (per 100,000 inhabitants) has been significantly higher for females than for males in the age group between 60 and 79 years old. The differences in gender may be due to a higher prevalence of cataract in female subjects [ 21 ]. This finding is similar to a study conducted in China, which showed that females had a significantly higher prevalence of visual impairment than men [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results also showed that female patients constituted more than 50% of all cataract surgery patients each year, and the age-adjusted rate of cataract surgery (per 100,000 inhabitants) has been significantly higher for females than for males in the age group between 60 and 79 years old. The differences in gender may be due to a higher prevalence of cataract in female subjects [ 21 ]. This finding is similar to a study conducted in China, which showed that females had a significantly higher prevalence of visual impairment than men [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This increasing incidence may be contributed by the increase in the elderly population because of improvement in healthcare [ 4 ]. It is estimated that the prevalence of cataract among the elderly population in Malaysia is up to 30% in which more cataract-related complications may arise, including LIG [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is comparable to other surveys in which LIG is detected on first consultation with the ophthalmologist [ 10 ]. It is best to counsel these patients about timely surgery in the second eye [ 8 ] to prevent similar complications. Efforts should continue to be done to increase accessibility to surgical care and to manage other contributing factors such as financial and social factors that prevent patients from going for cataract operation [ 1 ].…”
Section: Discussionmentioning
confidence: 99%